2022
DOI: 10.1186/s12890-022-01821-6
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal stenosis in prolonged mechanically ventilated patients: prevalence, risk factors, and bronchoscopic management

Abstract: Background Various complications may arise from prolonged mechanical ventilation, but the risk of tracheal stenosis occurring late after translaryngeal intubation or tracheostomy is less common. This study aimed to determine the prevalence, type, risk factors, and management of tracheal stenoses in mechanically ventilated tracheotomized patients deemed ready for decannulation following prolonged weaning. Methods A retrospective observational study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 42 publications
0
17
0
1
Order By: Relevance
“…10 Airway obstruction following prolonged weaning is typically a consequence of granulation tissue forming at the site of the internal stoma. 11,35 Interventional bronchoscopy proved safe and effective in treating such tracheal stenoses, 11 explaining why airway obstruction accounted for only a small number of failed decannulations in the present analysis.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…10 Airway obstruction following prolonged weaning is typically a consequence of granulation tissue forming at the site of the internal stoma. 11,35 Interventional bronchoscopy proved safe and effective in treating such tracheal stenoses, 11 explaining why airway obstruction accounted for only a small number of failed decannulations in the present analysis.…”
Section: Discussionmentioning
confidence: 69%
“…coughing), and (5) exclusion of airway obstruction (through flexible endoscopy of the upper airways, subglottic region, and trachea). 11 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tracheal diseases are still present, and the majority of them are associated with iatrogenic causes or trauma. For example, 1–3% of intensive care unit patients undergoing ventilation develop tracheobronchitis and up to 21% of intubated patients, and specifically 32% of patients with tracheostomies, develop tracheal stenosis [ 2 , 3 ]. Moreover, a study that was conducted in Germany by Schibilsky et al in 2020 showed that traumatic tracheobronchial injuries have a very high risk of mortality and mostly occur in males secondary to blunt trauma during accidents [ 4 ].…”
Section: Introductionmentioning
confidence: 99%